Soplos cardíacos fisiológicos y patológicos en el caballo de deporte. Su diagnóstico diferencial - Pidal, G. (2010)
The authors describe the guidelines used to improve the differential diagnosis between physiological and pathological murmurs in horses, particularly those used in equestrian sports. They also present the incidence of functional murmurs, valve affected and use of the horse found in the population studied. Finally refer to "diagnostic error" in the classifi cation of murmurs (pathological / physiological) when studied by clinical evaluation (auscultation) and after the use of complementary studies as bidimensional echocardiography and cardiac Doppler.\n